HISTOPATHOLOGICAL ANALYSIS OF COLORECTAL CANCER SPECIMENS IN A TERTIARY HOSPITAL IN PUDUCHERRY: A PROSPECTIVE STUDY - S, REVATHY; J, JEYASHAMBAVI; R, JAWAHAR; KP, UMADEVI; N, PRITHIVIRAJ (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: According to GLOBOCAN 2020, colorectal cancer is the fourth most lethal cancer in infected patients worldwide, with 1.7 million new cases recorded each year. When we look at Indian population studies, their mortality, incidence, and prevalence rates are consistently increasing compared to other European countries. Only a few studies have been reported on the clinical profile of CRC in India. Compared to females, males are more affected. This study was carried out to study the age, sex, and size distribution of malignant colon cancer and correlate the histopathological spectrum of colonic biopsies with clinical findings. Methods: Our study was a unicenter-based prospective study carried out over 2 years. All colonoscopic biopsies have been received in the Department of pathology, Aarupadai Medical College, and Hospital. Colonoscopies biopsies and colonic resection specimens are routinely fixed with 10% formalin and processed through an automatic tissue processor. Further, slides were stained with hematoxylin and eosin stains and examined for microscopic examination. Data generated from microscope observation were used for statistical analysis. Results: Our study included 54 patients with colorectal cancer. Among the patients, males were outnumbered by female patients, having an M: F ratio of 1:7:1. The most common age group affected is between the ages of 61 and 70. Adenocarcinoma was the most common histological malignancy (83%), followed by mucinous adenocarcinoma (7%), neuroendocrine carcinoma (4%), signet ring cell carcinoma (4%), and malignant melanoma (2%). Conclusion: Histopathological evaluation is the gold standard for the early detection of the gastrointestinal tract diseases, especially malignant diseases, which helps in the early prevention measures. Further, detailed studies on immunohistochemistry and molecular studies on colonoscopy biopsy specimens should be done in constant correlation with clinical features to help early detection of CRC and therapeutic prognostic purposes.